Penggunaan Media Peta Konsep Pada Mata Kuliah Materi dan Pembelajaran PKn di SD Sebagai Upaya meningkatkan Keaktifan Mahasiwa Program Studi S1-PGSD - Kurniawan, Agung (Penerbit STKIP PGRI Bangkalan, 2018)
The purpose of this research is to know the liveliness of students of Prodi S1-PGSD Universitas Terbuka Surabaya study group Bojonegoro. In the first cycle In the implementation phase of the improvement of learning cycle I, only 58.3% of students who have active learning is not successful. There are still some students who do not have activeness in learning so that the results of learning also can not be said either. In cycle II the lecturer modifies the concept map created. In addition, the lecturer also adds the final discussion of the material. With this activity there is an increase of student activeness that is 83,3% of students who have activity and influence on student learning value which increase